Technical and Vocational Education and Training College Female Students’ Experiences in Engineering Disciplines - Machaka, Mokgadi Elsa; Singh-Pillay, Asheena (Journal of Technical Education and Training, 2025)
The underrepresentation of women in engineering impedes the achievement of gender equity within the South African technical workforce. The engineering profession is integral to national economic and industrial development; however, structural and socio-cultural inequities are exacerbated due to gender imbalances. This study employs Schlossberg’s Transition Theory as an analytical framework to examine how female students navigate their educational journeys within traditionally male-dominated engineering programmes. The research question that guided this qualitative study was: What are the lived experiences of female students enrolled in engineering programmes at the Technical and Vocational Education and Training (TVET) college in South Africa? Open-ended questionnaires, focus group interviews, individual interviews, and collages were used to collect data from twenty-one purposively selected female engineering students. On the one hand, the findings highlight the influence of entrenched cultural norms, scarcity of female role models, institutional biases, and limited gender-responsive pedagogies. On the other hand, it documents the resilience strategies female students employ to navigate and persist within male-dominated learning spaces. The findings signal contextually relevant information for reforming engineering education at the TVET level, such as embracing inclusive teaching methods, establishing focused support systems, and cultivating supportive environments that promote belonging and achievement These findings undergird future conversations on gender equality in science, technology, engineering, and mathematics (STEM) and support national goals like the National Development Plan, aimed at increasing and diversifying South Africa’s engineering capabilities.